Manajemen Strategik sebagai Paradigma Baru dalam Organisasi Pendidikan - Muhamad Baedowi (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2022)
The purpose of this research is to find out the principles, advantages and benefits of strategic management in the world of education. In this study using literature research through descriptive analysis. From the results of this study resulted that the principle in strategic management is the existence of a strategy formulation that reflects the true desires and goals of the organization; there is a strategy implementation that describes how to achieve the goal (technically the implementation strategy reflects the ability of the organization and its allocation including in this case the financial allocation; strategy evaluation (evaluation strategy) which is able to measure, evaluate and provide feedback The benefits of organizational performance behind boarding school learning management in terms of: planning, implementation and evaluation The benefits include: productivity, high efficiency, has a ruthless position, mechanical advantage, human resource development, helpful work environment, created morale and social obligations. of the implementation of strategic management are: Associations become dynamic, control work runs well and competently, removes contrasts and conflicts in recognizing greatness, makes it easier to decide on changes or methodological improvements to be carried out, Empowers proactive behavior for all meetings to take part n Recognizing greatness and extending the sensation of having a place, dynamic cooperation and obligation about every authoritative part.